From Creativity to Innovation: The Role of Female Employees’ Psychological Capital - Asbari, Masduki; Prasetya, Agustian Budi; Santoso, Priyono Budi; Purwanto, Agus (IJOSMAS, 2021)
This study aimed to measure the effect of psychological capital and individual creativity on employee individual innovation behavior of the female employees of a manufacturing industry in Tangerang. In this study, individual creativity is mediating variable. Data was collected from 277 returned questionnaire of samples taken by random sampling. Data was analyzed using SEM method with SmartPLS 3.0 software. The results of this study showed that psychological capital had a significant effect on individual creativity, psychological capital and individual creativity have a significant effect on individual innovation behavior, individual creativity have a positive and significant effect on the relationship between psychological capital and individual innovation behavior. Individual creativity functioned as a partial mediator. This new research proposed a model for managing the individual innovation behavior among the female employees of the manufacturing industry in Tangerang through developing psychological capital with individual creativity as a mediator. This research could pave the way to improve employee readiness in facing the era of industrial revolution 4.0.